Traumatic memory in Eve Ensler’s The apology (2019) - Domines Veliki, Martina (ELOPE (Ljubljana), 2025)
Eve Ensler’s memoir The Apology (2019) traces Ensler’s growing up with an abusive father who raped her during her childhood and never apologized for the damage he caused. Ensler, now a successful woman in her sixties, thus imagines her father’s apology and details everything she was going through. Unlike Caruth’s theory of traumatic aporia where painful experiences are inherently contradictory and can never be grasped completely, Ensler’s act of writing the unspoken words of her father points to the fact that trauma can be healed through writing. As Richard McNelly and Joshua Pederson claim, it is precisely through writing that the victim can gain control over the act of recalling, helping the survivor to remake the self. Thus, in Ensler’s memoir, Caruth’s traumatic amnesia is replaced by the power of remembered and written detail to enact healing. This essay addresses issues of incest and rape through the lens of more recent trauma theory by paying attention to an imagined act of the perpetrator’s apology. By evoking pseudo memories, Ensler tries to understand her childhood trauma and how it affected her as a person. She establishes herself as a truth-teller and the survivor of intergenerational trauma with the ability to break the cycle of abuse, which is exactly what she does by writing The Apology.
Keywords: art as a form of self-expression; childhood trauma/pain; concept of time; disociacija; dissociation; memory; otroška travma/bolečina; pojem časa; spomin; umetnost kot oblika izražanja sebe